2012
DOI: 10.1179/1743132812y.0000000013
|View full text |Cite
|
Sign up to set email alerts
|

Time course of neuroprotection induced by normobaric hyperoxia in focal cerebral ischemia

Abstract: In the model of transient focal cerebral ischemia, hyperoxia preconditioning induced effective but transient neuroprotective effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Apparent preconditioning can also be produced with hyperoxia,(Bigdeli et al, 2012) and hypercarbia/acidosis. (Ladilov, 2012; Tregub et al, 2016) These observations suggest that the blood gas derangements we anticipated might be associated with dysfunctions years later, can also provide neuroprotective benefits, and it is the balance between injury and these benefits that determines what we see.…”
Section: Discussionmentioning
confidence: 99%
“…Apparent preconditioning can also be produced with hyperoxia,(Bigdeli et al, 2012) and hypercarbia/acidosis. (Ladilov, 2012; Tregub et al, 2016) These observations suggest that the blood gas derangements we anticipated might be associated with dysfunctions years later, can also provide neuroprotective benefits, and it is the balance between injury and these benefits that determines what we see.…”
Section: Discussionmentioning
confidence: 99%
“…Finite normobaric and hyperbaric hyperoxia can induce preconditioning in various experimental models [13], [68], and it has been especially investigated in neuroscience [69], [70]. A study showed that hyperoxic preconditioning (100% O 2 ) protected mesenchymal stem cells from subsequent hypoxia and downregulated caspases 1, 3, 6, 7 and 9 [71].…”
Section: Non-linear Response To Physiological Agentsmentioning
confidence: 99%
“…26,29 There have also been benefits observed following cerebral ischaemia in rats, where arterial hyperoxaemia may provide a degree of neuroprotection. 27,28,30…”
Section: Can Hyperoxaemia Cause Harm?mentioning
confidence: 99%
“…There is also some evidence that hyperoxaemia may improve outcomes in some scenarios. [26][27][28] Following acute myocardial infarction, Bartorelli et al 26 found decreased infarct size and improved left ventricular function when angioplasty reperfusion was used with adjunctive hyperoxia. Both hyperbaric oxygen therapy and, more practically, aqueous oxygen delivery showed these benefits.…”
Section: Can Hyperoxaemia Cause Harm?mentioning
confidence: 99%